Digitalisasi Proses Pengadaan Barang dan Jasa Menggunakan Jurnal Mekari Pada PT. Sarana Remaja Mandiri - Rizky Hutama Putra Haqq; Ahmad Ferdiansyah Pratama Putra; Moch Raffli Trio Romadhoni; Muhammad Irvan Arizqullah; Dika Ayu Safitri (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Procurement process in the industrial sector is undoubtedly conducted. However, conventional procurement of goods and services still faces numerous challenges, such as the need for physical storage space which is impractical, consumes a lot of space, and the difficulty in accessing past documents. With the advancement of the Industry 4.0 era, it pushes the procurement sector to undergo changes related to data integration systems and also the procurement process, all aimed at creating efficiency in the procurement of goods and services.